THE EFFECT OF WORK MOTIVATION AND WORK ENVIRONMENT ON PERFORMANCE MEDIATED BY JOB SATISFACTION - Michael Michael; Eka Desy Purnama; Adrie Frans Assa (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This study is to determine the effect of work motivation and work environment on performance mediated by job satisfaction, which was conducted at PT. Maybank Indonesia Finance, research respondents are employees of the Credit Marketing Officer. Total population 360 employees. Sampling of 78 respondents. Data collection is primary data source and secondary data source. Data analysis using SmartPLS-SEM (Partial Least Square–Structural Equation Modeling) software. The results of the study that there is no significant effect of work motivation on performance, there is a significant effect of work environment on performance, there is a significant effect of work motivation on job satisfaction, there is a significant effect of work environment on job satisfaction, there is a significant effect of job satisfaction on performance, there is a significant effect of job satisfaction in mediating work motivation on performance, there is a significant effect of job satisfaction in mediating the work environment on performance.